Effects of Seed Fraction on Sowing Quality and Yield of Three-Line Hybrid Maize - Katarzyna Panasiewicz; Rafał Sobieszczański; Karolina Ratajczak; Agnieszka Faligowska; Grażyna Szymańska; Jan Bocianowski; Anna Kolanoś; Rafał Pretkowski (Agriculture)
Maize is one of the most productive cereal crops, and is increasingly being grown over large areas. Using the right cultivar of high-quality selected seeds for sowing can be crucial for its productivity. The aim of this study was to investigate the effect of kernel fraction on the seed quality, seed vigor, morphological traits, and seed yield of the trilinear hybrid maize cv. ‘Lokata’. The research factor was the kernel fraction, categorized based on the thousand-kernel weight (TKW) into four groups: I—small; II—medium; III–large; and IV–very large. A three-year experiment showed that increases in the TKW resulted in increases in germination and vigor up to fraction III (large seeds) in maize. Sowing maize seeds with a higher TKW resulted in plants with higher fresh and dry weights in the early stages of maize development; however, this response decreased as growth progressed. The seed yield was significantly correlated with plant height and the number of kernels per cob for all fractions sown, but the fraction did not significantly modify the seed yield of ‘Lokata’ maize.